An embryonic stem cell-specific heterochromatin state promotes core histone exchange in the absence of DNA accessibility - Carmen Navarro (Nature Portfolio, 2020)
Nucleosome turnover concomitant with incorporation of the histone variant H3.3 is a hallmark of regulatory regions in the animal genome. Here, the authors demonstrate that fast histone turnover and H3.3 incorporation defines a dynamic heterochromatin state in pluripotent stem cells.